Pengembangan Modul Matematika Diskrit Berbasis ARIAS pada Mahasiswa Teknik Informatika - Indana Lazulfa; Dharma Bagus Pratama Putra (Jurnal Pendidikan Matematika:Judika Education, 2020)
This research aims to develop modules based on ARIAS learning models, to improve learners' learning motivation, as well as student competencies. So it will be found that meets the criteria of effectiveness, practicality and validity of the module based on ARIAS. The development model refers to the development of Borg and Gall which consists of two main parts namely designing modules and validating modules. To validate the module is carried out a validity test, a practicality test and an effectiveness test. Research Results, validation test conducted by material experts and media experts with results of 86.02 and 82.47 to meet the criteria of validity. The practicality test was carried out by practicing lecturers and 4 students obtained grades of 81.75 and 86 so that they entered practical criteria. Test effectiveness using one-group-pretest-posttest and obtained N-Gain¬ 60.95 so that it is included in the criteria is quite effective. In conclusion, discrete math modules based on arias learning models developed are feasible to be used in the sense of valid, practical and effective use, proven to increase the motivation of learners' learning, as well as the competence of learners. Keywords: ARIAS, Discrete Mathematics, Module Development.